(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Windadri FI. 2023. Moss from Sumbawa District, Indonesia. Biodiversitas 24: 661-669. Plant diversity in the Lesser Sunda Islands has been widely studied, but it still needs to be carried out on Sumbawa Island. The study aimed to determine the diversity of moss species from the island, especially in the Sumbawa District. The exploration method was used in this research activity, that is conducting exploration, taking research samples and observing habitats at the research site. The distribution tracking was conducted to determine the status of each moss species from the research site. The results recorded 41 species of mosses from the research site in 24 genera and 14 families. Fissidentaceae is one of the moss families, had the highest species diversity in the study site, and was previously never reported from Sumbawa Island. In contrast, the common species was Tortula muralis. The study of moss species from the study site revealed that four species had been found in previous moss collections, namely Anoectangium aestivum, Neckeropsis lepineana, Pinnatella alopecuroides, and Octoblepharum albidum. Several mosses from the study site contributed to the moss diversity of Sumbawa Island as new records. The number of moss from the study site and as new records status is 37 species for Sumbawa Island, 18 species for Lesser Sunda Islands, and six species for Indonesia, respectively.